2010
DOI: 10.1017/s0033822200045495
|View full text |Cite
|
Sign up to set email alerts
|

Establishing a Firm Chronological Framework for Neolithic and Early Dynastic Archaeology in the Shangluo Area, Central China

Abstract: Technological and theoretical advancements in modern radiocarbon chronology make the precise dating of archaeological and geological events possible. Here, we show examples of how these state-of-the-art methods can be used to establish and refine the archaeological cultural chronology for the Shangluo area in the Qinling Mountains of central China. In this study, the Donglongshan and Zijing sites were dated using the high-precision accelerator mass spectrometry (AMS) 14C method. Also, detailed magnetic-suscept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 42 publications
(37 reference statements)
0
4
0
Order By: Relevance
“…The 14 C dates of the low-temperature and high-temperature fractions (Zhu et al 2010) are given in Table 1, The δ 13 C values of the HT and LT fractions obtained in the present study as shown in the Table 2. All 14 C dates of the low-temperature are younger than hightemperature fractions, and δ 13 C values of the HT are less negative than LT, resulting from change of carbon source instead of fractionation.…”
Section: Resultsmentioning
confidence: 69%
“…The 14 C dates of the low-temperature and high-temperature fractions (Zhu et al 2010) are given in Table 1, The δ 13 C values of the HT and LT fractions obtained in the present study as shown in the Table 2. All 14 C dates of the low-temperature are younger than hightemperature fractions, and δ 13 C values of the HT are less negative than LT, resulting from change of carbon source instead of fractionation.…”
Section: Resultsmentioning
confidence: 69%
“…Subsamples for radiocarbon analyses were pretreated following Zhu et al []. After removing visible roots and litters, bulk wet soil samples were soaked in deionized water overnight and then transferred to an ultrasonic bath for 30 min to allow a complete dispersion and homogenization.…”
Section: Methodsmentioning
confidence: 99%
“…Cryogenically purified CO2 was converted to the target using the hydrogen-iron reduction method. This method was described in detail by Zhu et al (2010).…”
Section: Laboratory Analysismentioning
confidence: 99%